2016
DOI: 10.1007/s00253-016-7682-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Corynebacterium glutamicum for fast production of l-lysine and l-pipecolic acid

Abstract: The Gram-positive Corynebacterium glutamicum is widely used for fermentative production of amino acids. The world production of L-lysine has surpassed 2 million tons per year. Glucose uptake and phosphorylation by C. glutamicum mainly occur by the phosphotransferase system (PTS) and to lesser extent by inositol permeases and glucokinases. Heterologous expression of the genes for the high-affinity glucose permease from Streptomyces coelicolor and Bacillus subtilis glucokinase fully compensated for the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 108 publications
0
69
0
Order By: Relevance
“…In this pathway, L‐lysine is oxidatively deaminated by L‐lysine 6‐dehydrogenase to yield α‐aminoadipic semialdehyde. After spontaneous cyclization to 1‐piperideine 6‐carboxylic acid (P6C), pyrroline 5‐carboxylate reductase, an enzyme of L‐proline biosynthesis encoded by proC , reduces P6C to L‐PA . We have previously shown that this pathway can be used for fermentative production of L‐PA by recombinant C. glutamicum .…”
Section: Introductionmentioning
confidence: 99%
“…In this pathway, L‐lysine is oxidatively deaminated by L‐lysine 6‐dehydrogenase to yield α‐aminoadipic semialdehyde. After spontaneous cyclization to 1‐piperideine 6‐carboxylic acid (P6C), pyrroline 5‐carboxylate reductase, an enzyme of L‐proline biosynthesis encoded by proC , reduces P6C to L‐PA . We have previously shown that this pathway can be used for fermentative production of L‐PA by recombinant C. glutamicum .…”
Section: Introductionmentioning
confidence: 99%
“…l -PA can be biosynthesized using crude enzymes or whole-cell biocatalysts [14, 15, 19], and several of the different catalytic steps involved have been investigated, including some that are unstable and accompanied by high manufacturing costs that limit their applications. However, few researchers have focused on the direct fermentation of l -PA, even though fermentation potentially offers an alternative, efficient, low cost method [22]. In the present study, we expanded the E. coli metabolic pathway by introducing a heterologous lysine cyclodeaminase that can biosynthesize l -PA directly from glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Wendisch et al, previously attempted to develop the l -PA producers by engineering the industrial lysine producer C. glutamicum to fermentatively synthesized l -PA from glucose via the P6C pathway through heterologous expression of lysine dehydrogenase ( lysDH ) and pyrroline 5-carboxylate reductase ( proC ) [22]. Although they fully optimized the glucose uptake system and achieved an acceptable level of by-product elimination, the l -PA titer, yield and productivity were low (below 1.9 g/L or 15 mM, 0.1 g/g and 0.05 g/L h, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations